Undergraduate nursing students' experiences of rationed nursing care - A qualitative study - Kalánková, Dominika; Bartoníčková, Daniela; Kirwan, Marcia; Gurková, Elena; Žiaková, Katarína; Košútová, Dominika (Nurse education today, 2021)
BACKGROUND: Nursing students are required to spend a significant portion of their educational preparation in clinical practice. Because of the prevalence of missed or rationed care, it seems irrefutable that students are exposed to rationed care during their practice placement, or that they contribute to its prevalence either actively or passively. OBJECTIVES: The study aimed to discover how nursing students interpret the concept of rationed care, and their experiences of rationing in practice. DESIGN: A descriptive qualitative study. PARTICIPANTS: Eighteen final year nursing students from three universities within the Slovak Republic. METHODS: Semistructured face-to-face interviews were conducted (n = 18). Data were analyzed using thematic analysis which resulted in the development of themes and subthemes. RESULTS: We identified three meaningful themes focused on the phenomenon of rationed care from the perspective of nursing students, namely Incomplete care is normalized; Provision of impersonal patient care; and the Existence of a hidden curriculum for practice placements. CONCLUSIONS: Student nurses were quite demanding about the learning experience during their clinical training. They are often frustrated by inconsistencies between their theoretical preparation and the realities of practice. They recognise difficulties for registered nurses in providing safe, high quality care in constrained circumstances, and although they are critical of this, they acknowledge their own acceptance of the situation. Based on this, students must establish an understanding of the theory behind, and reasons for rationed care before commencing clinical placement. A greater understanding would enable students to develop strategies for coping with inconsistencies and voicing concerns.
Keywords: studenti ošetřovatelství; studium ošetřovatelství bakalářské; ošetřovatelská péče; kvalitativní výzkum; přidělování zdravotní péče; Rationed care; lidé; Quality of care; Nursing Care; Education, Nursing, Baccalaureate; Qualitative Research; Patient safety; Slovenská republika; Humans; Students, Nursing; Health Care Rationing; Students; Nursing; Slovakia